Effect of information sharing and capacity adjustment on healthcare service supply Chain: The case of flood disaster - Anjomshoae A.; Hassan A.; Samuel C.; Yew W.K. (My University, 2025)
In recent years, flood has becoming disastrous events in Malaysia causing loss of lives and properties. The damages brought by flood is partly due to lack of appropriate preparedness and effective responses toward such events. Several researchers have reported studies on flood preparedness and response. However, their studies lack of holistic views. This research attempted to holistically analyze the evacuation planning and flood preparedness. A system dynamic model consisting of an evacuation sub-model and a medical service supply sub-model were developed based on historical hydrological data for Kelantan River basin in Malaysia. Decisions on evacuation can be made based on river level and flood risk information. The efficiency of the medical service supply model is showed through the Bullwhip Effect. The effect of information sharing together with capacity adjustment on the bullwhip effect were studied. The results of this research indicates that reducing delay time to provide medical resources to evacuees need and sharing demand information in the upstream medical supply model yields better performance. © IEOM Society International. © IEOM Society International.